2022
DOI: 10.1108/ijchm-08-2021-0975
|View full text |Cite
|
Sign up to set email alerts
|

A hotel stay for a respite from work? Examining recovery experience, rumination and well-being among hotel and bed-and-breakfast guests

Abstract: Purpose This paper aims to examine the relationship among guests’ lodging recovery experience, work-related rumination, guest satisfaction and well-being, within the context of hotels and bed and breakfasts (B&Bs). Design/methodology/approach The sample included 823 Taiwanese full-time workers. The proposed relationships were tested using partial least square structural equation modeling, and the moderating effects of accommodation types were tested using multi-group analysis. Findings The research fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 68 publications
0
13
1
Order By: Relevance
“…The recent trend in wellness tourism reflects potential overlap between wellness tourism and medical tourism that opens doors for tourists to access a variety of HWB treatments. The findings of this review differ from previous studies exploring the associations among health treatments, the restorative experience of hotels (Chen et al , 2022) and conventional tourist attractions for tourist HWB. This review reveals unique attributes of wellness tourism that unravel how tourists expect wellness tourism that may act as a torchbearer to develop an efficient marketing strategy.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The recent trend in wellness tourism reflects potential overlap between wellness tourism and medical tourism that opens doors for tourists to access a variety of HWB treatments. The findings of this review differ from previous studies exploring the associations among health treatments, the restorative experience of hotels (Chen et al , 2022) and conventional tourist attractions for tourist HWB. This review reveals unique attributes of wellness tourism that unravel how tourists expect wellness tourism that may act as a torchbearer to develop an efficient marketing strategy.…”
Section: Discussioncontrasting
confidence: 99%
“…Moreover, tourists expect the provision of ambient lodging and state-of-the-art hospitality service during their stay at host destinations (DeMicco, 2017a; Mueller and Kaufmann, 2001; Pani and Das, 2015; Smyth, 2005; Williams, 2010). Hotel stay experience with wellness facilities, such as steam bath, sauna, massage and healthy diet, has restorative effects on guest HWB (Chen et al , 2022). Tourists expect hygienic food and recreational activities during their wellness tourism to improve their HWB (Cormany, 2017; DeMicco, 2017a; Majeed and Ramkissoon, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The effects of intrapersonal (such as bodily feeling and self-making) and interpersonal (such as family ties and community) dimensions of existential authenticity remain to be investigated. Well-being is an important concept in wellness tourism research (Chen et al , 2022; Varga et al , 2021). This study proposed an integrated model based on the SOR model and found, accordingly, that well-being plays the role of response in this model.…”
Section: Discussionmentioning
confidence: 99%
“…Such a large and sudden disturbance to daily life is likely to have a major negative impact on human well-being, especially for those living in densely populated cities. A recent study [ 10 ] of 823 full-time workers in Taiwan revealed that a simple hotel stay provides a respite from work and reduces work-related rumination, thereby contributing to guest satisfaction and both hedonic and eudaimonic well-being. These invisible life pressures make people want to capture a little happiness in their lives, and eating delicious food in a restaurant is one expedient way of meeting this need.…”
Section: Introductionmentioning
confidence: 99%